Industrial espionage: The dark side of the "Digital Age" - Nodoushani, O.; Nodoushani, P.A. (Competitiveness Review, 2002)
Amid all enthusiasm regarding the rise of the Digital Age, industrial espionage remains the dark side of the post-industrial revolution. The Federal Industrial Espionage Act of 1996 aimed at leveling the field regarding widespread cheating and stealing of intellectual properties by competitors in the marketplace. In this paper we aim at defining various forms of industrial espionage in the light of the ongoing information technology revolution. © Emerald Backfiles 2007.
4 citations (Crossref) [2023-10-31]
Keywords: dept.mgt

The strategic management of research and development - Nodoushani, Omid; Nodoushani, Patricia A (Journal of Comparative International Management, 2002)
Citation Key Alias: lens.org/051-498-885-514-43X tex.type: [object Object]
Keywords: dept.mgt; ⛔ No DOI found

Book Review: Resource ReviewsTaking center stage: masterful public speaking using acting skills you never knew you had, by GottesmanDeb and MauroBuzz. new york, NY: berkley books, 2001. 191 pages, soft cover. - Oppedisano, Jeannette (Academy of Management Learning and Education, 2002)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/127-128-939-707-091 tex.type: [object Object]
Keywords: book.review; dept.mgt